Fatigue delamination propagation: Various effects on results - Singh, Anuwedita; Aizen, Snir; Mega, Mor; Rifkind, Shira; Banks‐Sills, Leslie (Fatigue & fracture of engineering materials & structures, 2024)
In this investigation, three subjects are considered. First, the effect of the human factor is examined. In carrying out analyses of fatigue delamination propagation tests on laminate composites, the delamination length must be measured. The human effect on measurement of the delamination length a by different investigators is discussed. A limited influence of the human factor on the measurement of the delamination length a, as well as on delamination propagation rate da/dN, is observed in this study. Secondly, the paper proceeds to discuss the influence of the R‐ratio on the fatigue delamination growth rate. It is found that a higher rate of crack/delamination propagation is associated with lower R‐ratios which appears to contradict conventional wisdom. This behavior is confirmed in tests. Thirdly, a comparison between the fatigue propagation rates of two material systems is considered. It is concluded that the energy release rate used to assess these materials should not be normalized. Highlights Impact of human factor on fatigue delamination tests in laminate composites. Limited influence of the human factor on delamination length and propagation rate. The lower the R‐ratio, the higher the delamination propagation rate. The crack driving force for laminates should be taken as GImax.